2013
DOI: 10.1039/c2dt32576d
|View full text |Cite
|
Sign up to set email alerts
|

Self-assembly of metallomacrocycles with dipyrazole ligands and anion sensing of [Pd4Fe2] macrocycle with ferrocene-based dipyrazole ligand

Abstract: By employing dipalladium corners [(bpy)(2)Pd(2)(NO(3))(2)](NO(3))(2) or [(phen)(2)Pd(2)(NO(3))(2)](NO(3))(2) (where bpy = 2,2'-bipyridine and phen = 1,10-phenanthroline) to bridge ferrocene-based dipyrazole ligand (L(1)) and m-phenylene-based dipyrazole ligands (L(2-3)) in aqueous solution, a series of positively-charged [M(4)L(2)](4+) metallomacrocycles were obtained. Their structures were characterized by (1)H NMR, electrospray ionization mass spectrometry (ESI-MS), elemental analysis, and single crystal X-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
7
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 54 publications
(6 reference statements)
0
7
0
Order By: Relevance
“…À salt of 54 that was obtained through anion exchange with 10-fold excess NH 4 PF 6 in a methanol solution) 22). 31 The structure of 59 was confirmed by X-ray crystallographic analysis, which revealed that the size of its inner square-shaped cavity was approximately 6 Â 11 Å (Fig. 22).…”
Section: Edge-functionalized Multiferrocenyl Metallacyclesmentioning
confidence: 84%
See 2 more Smart Citations
“…À salt of 54 that was obtained through anion exchange with 10-fold excess NH 4 PF 6 in a methanol solution) 22). 31 The structure of 59 was confirmed by X-ray crystallographic analysis, which revealed that the size of its inner square-shaped cavity was approximately 6 Â 11 Å (Fig. 22).…”
Section: Edge-functionalized Multiferrocenyl Metallacyclesmentioning
confidence: 84%
“…34). 41 Multinuclear NMR { 1 H and 31 P} spectroscopy, elemental analysis, and ESI-MS results provided strong evidence for the formation of multi-ferrocenyl cuboctahedron 94. For example, the 31 P { 1 H} NMR spectrum of 94 displayed a sharp singlet (B16.9 ppm) shifted upfield from that of the starting platinum acceptor 21 by B6.0 ppm.…”
Section: Exo-functionalized Multiferrocenyl Metallacagesmentioning
confidence: 97%
See 1 more Smart Citation
“…In recent decades, mechanoresponsive luminescent (MRL) materials have received a large amount of attention arising from their intrinsic nature, daedal structures, and characterization, as well as their potential applications. Broadly, changes in crystal structure resulting from external mechanical stimulation led to luminescence changes. For the aryl gold­(I) isocyanide compounds that exhibit MRL properties, the luminescence changes mainly refer to changes of halogen bond interactions and π···π interactions in the crystal structure. Upon mechanical stimulation, a single-crystal-to-single-crystal phase transition accompanied by red-shifted or blue-shifted photoluminescence with incorporated weak or strong C–H···π interactions was reported by Ito . The same author also utilized chiral steric hindrance paired with aurophilic interactions to cause a chiral-crystal-to-achiral-crystal phase transition, which accompanied a change of emission properties .…”
mentioning
confidence: 99%
“…Thus, a one-pot, two-step, three-component synthesis was expected to provide unprecedented yet convenient access to 4-(1-ferrocenyl­alkyl)­pyrazoles, particularly chiral ones. It is noteworthy that some 4-(ferrocenyl­methyl)­pyrazole/metal complexes exhibit growth inhibitory activity against human cancer cell lines, promising anion-sensing properties, and interesting electrochemical behaviors . These simple 4-(ferrocenyl­methyl)­pyrazoles were reported to be prepared in two steps by substitution of ferrocenyl­methanol with 1,3-diketones followed by condensation with hydrazine.…”
mentioning
confidence: 99%